2014
DOI: 10.2525/ecb.52.211
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Deposition of Nutrients Shifts Carbon Capture and Storage Trends in Freshwater Tropical Lakes in India

Abstract: An understanding of ongoing changes in biogeochemistry of carbon (C) as influenced by increasing atmospheric deposition (AD) of nutrients is important for integrated water resource management and for exploring options for balancing C sink and fluxes. To determine whether AD-nutrients would increase phytoplankton production and catchment carbon flushing in lakes, we analyzed NO 3 , NH 4 and PO 3 4 in atmospheric deposits, microbial biomass and activity in catchment, nutrient and dissolved organic carbon (DOC) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Extreme precipitation events (which is increased in the region during recent years) have enhanced N loading from terrestrial watershed to the lakes consisting of vegetational debris and animal waste. Increase in nitrate concentration can also take place as a result of anthropogenic disturbances andenhanced microbially fixed-N (Pandey and Verma, 2004). A remarkable observation in the study is the amplification of N:P ratio i.e.…”
Section: Resultsmentioning
confidence: 84%
“…Extreme precipitation events (which is increased in the region during recent years) have enhanced N loading from terrestrial watershed to the lakes consisting of vegetational debris and animal waste. Increase in nitrate concentration can also take place as a result of anthropogenic disturbances andenhanced microbially fixed-N (Pandey and Verma, 2004). A remarkable observation in the study is the amplification of N:P ratio i.e.…”
Section: Resultsmentioning
confidence: 84%
“…Earlier studies have shown a consistently rising trend in AD input and lateral transport of nutrients to lakes and rivers in many parts of India. 5,8,22 Intensive studies conducted in the middle segment of Ganga River 5,6 showed that AD input contributes, almost on similar spatiotemporal scale, large fluxes of DIN and DRP as direct deposition and through land surface runoff to the river.…”
Section: Discussionmentioning
confidence: 99%
“…6 In seasonally dry tropical regions of North India, extensive landscape transformation accompanied by massive use of fertilizers with urban-industrial factors drastically influences the aquatic ecosystem functioning. 7,8 Water bodies with naturally low N or P are highly sensitive to the external input of these nutrients. 9 The N:P ratio (referred to as Redfield ratio) is an important indicator of which nutrient is limiting the phytoplankton growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation